The Effect of Peatland Conversion on Surface Temperature in Bengkalis Regency Riau Province - Hayati, Zahrotal; Ahyuni, Ahyuni; Wilis, Ratna (Sumatra Journal of Disaster, Geography and Geography Education, 2019)
This study aims to determine the effect of peatland conversion on surface temperature In Bengkalis Regency, Riau Province. Data obtained from Landsat imagery in 1988, 1996, 2000 and spot imagery 6 in 2016. The methods used to determine land cover and surface temperature are spatial analysis methods using GIS and Remote Sensing, while determining the correlation between land cover and surface temperature using simple linear regression. Peatlands in Bengkalis Regency around 580,631.64 Ha (66.38% of Bengkalis Regency), the forest cover on peatland in 1988 covered 464.504,7 Ha (79.99%), non forest covered 115,069.5 Ha (19.81%), in 1996 forests covered 448,473.9 Ha (71.65%), non forest 131,114 Ha (22.58%). In 2000 forest covered 416,043.9 Ha, (71.65%) non forest covered 163,450.9 Ha (39,81%). In 2016 the forest covered 23,168.4 Ha (39.81%) and non forest 347,853.4 Ha (59.90%). The protected peatlands with thickness of ≥ 300 Cm covered 242,680.37 Ha (41.79% of the peatland in Bengkalis Regency), in 1988 the forest cover on the protected peatland covered 224,814.9 Ha (92.68%) and non forest covered 17,865.47 Ha (7.32%), but in 2016 the forest covered 148,171.72 Ha (61.21%) and non forest 94,501.65 Ha (38.79%), so that the forest cover on peatland converted from 1988 to 2016 was 233,336.7 Ha (40.19% of the total area of peatland) and the protected peatlands converted 76,643.18 Ha (31.58% of the area protected or 13% of the whole area of peatland). The forest Change on 1 Km2 of peatland caused the increasing on average 0.50 oC of surface temperature.